A comparative analysis of livelihood sustainability among farmers in Ca Mau Province, Vietnam: a case study of organic mangrove–shrimp and rice–shrimp farming systems - Hieu Hong Hua; Duyen My Chau; Thuy Thanh Thi Ngo; Man Le Nguyen (Cogent Social Sciences)
Mangrove-shrimp and rice-shrimp farming are vital organic models supporting shrimp farmers’ livelihoods in Ca Mau, a coastal province in Vietnam’s Mekong Delta. This study examines the livelihood capital farmers utilize to implement these aquaculture systems, examining the methods employed, benefits gained, and strategies to address challenges of achieving sustainable livelihoods. The finding of focus group discussions (FGDs), key informant interviews, and household surveys show that farmers possess adequate livelihood capital to engage in both the mangrove–shrimp and rice–shrimp systems. Notably, net income per hectare from the rice–shrimp model exceeds that from the mangrove–shrimp model. However, climate variability and water quality issues significantly impact farming practices. The study identifies the need for improved infrastructure, particularly road development linking local and national markets, as a crucial recommendation from farmers and local authorities. Additionally, implementing water management strategies at the commune level emerges as a viable intervention to mitigate environmental pollution risks. This research underscores the importance of sustainable aquaculture practices, offering insights applicable to similar farming systems worldwide. Future research should focus on large-scale surveys and technical assessments of soil and water quality, facilitating comprehensive socio-economic and environmental analyses of these organic shrimp farming systems.